2018
DOI: 10.1097/ta.0000000000001801
|View full text |Cite
|
Sign up to set email alerts
|

Use of French lyophilized plasma transfusion in severe trauma patients is associated with an early plasma transfusion and early transfusion ratio improvement

Abstract: Therapeutic, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…There were also significantly less cases of massive transfusion utilization and RBC transfusion in the FLyP group compared to the FFP group (7 vs. 45%). No differences in hospital length of stay, ICU length of stay, or 24-h mortality between the two groups were noted [87].…”
Section: French Lyophilized Plasma (Flyp)mentioning
confidence: 84%
See 1 more Smart Citation
“…There were also significantly less cases of massive transfusion utilization and RBC transfusion in the FLyP group compared to the FFP group (7 vs. 45%). No differences in hospital length of stay, ICU length of stay, or 24-h mortality between the two groups were noted [87].…”
Section: French Lyophilized Plasma (Flyp)mentioning
confidence: 84%
“…A dried plasma product introduced in the USA will allow for earlier plasma administration starting prehospital and continuing into the hospital setting, which will likely improve patient outcomes, as demonstrated by the French experience [87]. Dried plasma should certainly replace the recommended crystalloid administration in the ATLS guidelines, which were designed to accommodate all levels of practice and take into account the variable availability of blood products.…”
Section: Future Of Lyophilized Plasmamentioning
confidence: 99%
“…Of the nine included studies, one study was an RCT comparing FDP to FFP , while eight studies were nonrandomized. Of the eight nonrandomized studies, two studies had a control group: one study compared FDP to FFP and one study compared FDP + RBC to whole blood . The six other studies were uncontrolled .…”
Section: Resultsmentioning
confidence: 99%
“…French lyophilized plasma (FLYP) has been used in military operations around the world and has also been authorized in France for civilian use in austere settings . A recent randomized trial indicated that the use of FLYP in trauma patients resulted in improved coagulation parameters and better early transfusion ratios compared to FFP . In July 2018, FLYP was approved by the FDA for limited use by the US military .…”
Section: Dried Plasma Is Most Urgently Neededmentioning
confidence: 99%
“…33 A recent randomized trial indicated that the use of FLYP in trauma patients resulted in improved coagulation parameters and better early transfusion ratios compared to FFP. 34,35 In July 2018, FLYP was approved by the FDA for limited use by the US military. 36 While meeting a short-term urgent need, this is considered a limited, temporary measure until a US product can attain FDA approval to meet the longer-term military requirement.…”
Section: Dried Plasma Is Most Urgently Neededmentioning
confidence: 99%